A statistical study of Weinmannia pollen trajectories across the Andes - Perez, Claudio Fabian (2009)
Recent airborne pollen records data from Northern Patagonia (San Carlos de Bariloche, Argentina, Lat.41.1435 S, Long. 71.375W, 800m elevation) suggest thatpollen transport takes place from the west to the east slope of the Andes. However, the atmospheric characteristics responsible of this transport have not yet been studied. Theaim of this paper is to assess potential source areas and to describe the involved atmospheric mechanisms of the trans- Andean pollen transport. Methodology relies on the analysisof backward trajectories of air masses calculated with the HYSPLIT 4.9 regional model for particular days where airborne pollen of Weinmannia trichosperma Cav. was detectedeast of the Andes. This pollen type was selected because it is found regularly at localities in eastern Patagonia beyond its present-day distribution. Weinmannia?s substantial presenceduring early Holocene times would also benefit from better knowledge of its transport mechanisms. Correspondence between atmospheric trajectories and the position of sourceswas checked using GIS maps. Mode T, Principal Component Analysis (PCA) with Varimax rotation was used to identify the main spatial structure of geopotential height anomaliesproducing the calculated trajectories. Eighty-eight cases showed that the calculated directions of trajectories trended from the Northwest to Southwest passing over the Chilean regionofW. trichosperma distribution. PCs results showed two patterns of negative anomalies over southern Patagonia. The prevailing circulation pattern which drives airborne transportis the presence of a trough located south of 37 to 40 S with its axis over western Patagonia. The synoptic situations for two cases highly correlated with principal component scoreswere described.